1994
DOI: 10.3109/10715769409056550
|View full text |Cite
|
Sign up to set email alerts
|

The Ambivalent Role of Glutathione in the Protection of Dna Against Singlet Oxygen

Abstract: Glutathione (GSH) was examined with respect to its ability to protect DNA against 1O2 damage. We have found that GSH protected, at least partly, the DNA against inactivation by 1O2. Up to 10 mM the protection increased as a function of GSH concentration. Above 10 mM the protection remained constant and less than expected on the basis of scavenging/quenching of 1O2, in contrast to the protection offered by sodium-azide. Especially at the higher concentrations of GSH the protection against the biological inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 17 publications
(2 reference statements)
2
33
2
Order By: Relevance
“…Also, the inhibitory effect of roscovitine must be considered not only on the cdk but also on RNA synthesis (Ljungman & Paulsen 2001). Because GSH is involved in multiple functions, including DNA and protein synthesis (Lafleur et al 1994), it could be expected that oocytes treated with roscovitine showed a higher GSH content than their counterparts, as was observed in our case since this functional activity of GSH was probably decreased.…”
Section: Discussionsupporting
confidence: 64%
“…Also, the inhibitory effect of roscovitine must be considered not only on the cdk but also on RNA synthesis (Ljungman & Paulsen 2001). Because GSH is involved in multiple functions, including DNA and protein synthesis (Lafleur et al 1994), it could be expected that oocytes treated with roscovitine showed a higher GSH content than their counterparts, as was observed in our case since this functional activity of GSH was probably decreased.…”
Section: Discussionsupporting
confidence: 64%
“…Several studies have shown that the addition of cysteamine to the oocyte maturation medium increases intracytoplasmic GSH levels in different species [14,17,18,[26][27][28]. GSH, the major non-protein sulphydryl compound in mammalian cells, is an endogenous and ubiquitous reducing agent that protects cells from oxidation and plays a number of important roles in cellular metabolism including protein synthesis and the reduction of disulphides [29]. In oocytes, intracytoplasmic GSH participates in the transformation of the fertilising sperm head in the male pronucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple actions have been described for GSH, including increasing amino acid transport, stimulating DNA and protein synthesis, reduction of disulfides and protection against toxic effects of oxidative damage (Meister, 1983;Lafleur et al, 1994). It has been demonstrated that adding beta m e r c a p t o e t h a n o l ( M E ) i n c r e a s e d intracellular GSH in the mo use lymphocytes (Zmuda and Friedenson, 1983).…”
Section: Introductionmentioning
confidence: 99%